PREVALANCE OF HELICOBACTER PYLORI IN PATIENTS WITH RENAL FAILURE - Ali Reşit BEYLER; Tülay SARIÇAM; Neval DUMAN; Murat DURANAY; Şükrü DUMLU; Enver ÜNER; Ali ÖZDEN (Turkish Journal of Gastroenterology, 2020)
-